2016
DOI: 10.1111/bjet.12475
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to teaching online: Exploring factors influencing teachers in a fully online university

Abstract: In recent years there has been widespread interest in the implementation of online courses in universities. While most studies about online learning environments primarily focus on technology‐related issues or instructional methods, little attention has been given to online teachers and their teaching approaches. The aim of this paper is to provide an overview of how teachers approach online teaching and the factors affecting individual teachers’ approaches to teaching online, particularly in a fully online un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 19 publications
1
42
1
7
Order By: Relevance
“…For instance, Alvarez et al (2009) categorized five roles of teachers: designer/planning role, social role, cognitive role, technological domain and managerial domain. Other generalizations include: pedagogical, social, managerial, and technical by Berge (1995); instructional design, organization, facilitating discourse and direct instruction by Anderson et al (2001); cognitive, affective, and managerial roles by Coppola et al (2002); administrative, personal, technological, instructional design, pedagogical, assessment and social roles by Varel (2007); online teacher roles of managing social interaction, instructional design, guiding the use of technology, learning assessment and learning support by Badia, Garcia & Meneses (2017). In fact, these roles overlap with each other and the overlapping theoretical classification becomes an obstacle for classroom teachers to understand their roles and examine precise functions and tasks related to teacher roles (Baran et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Alvarez et al (2009) categorized five roles of teachers: designer/planning role, social role, cognitive role, technological domain and managerial domain. Other generalizations include: pedagogical, social, managerial, and technical by Berge (1995); instructional design, organization, facilitating discourse and direct instruction by Anderson et al (2001); cognitive, affective, and managerial roles by Coppola et al (2002); administrative, personal, technological, instructional design, pedagogical, assessment and social roles by Varel (2007); online teacher roles of managing social interaction, instructional design, guiding the use of technology, learning assessment and learning support by Badia, Garcia & Meneses (2017). In fact, these roles overlap with each other and the overlapping theoretical classification becomes an obstacle for classroom teachers to understand their roles and examine precise functions and tasks related to teacher roles (Baran et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, most of the research is dominated by qualitative studies ranging from case studies, collaborative action research and grounded theory (Izadinia, 2015;Li & Ni, 2011;Subramaniam, 2010;Scott, 2013;Tran & Nguyen, 2015;Donnelly, 2013). In contrast, quantitative studies that examine teacher roles and relevant teaching behaviors in online learning contexts are scarce (Alvarez, Guasch & Espasa, 2009;Lee, 2011;Badia et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…De todas formas, creemos que es necesario capacitar a los docentes para que adquieran competencias para desarrollar actividades a partir de los materiales de lectura. Por otra parte, se confirma lo expresado por diferentes autores (Badia, et al, 2017;Luo, et al, 2017; Ramírez y Barajas, 2018) respecto a que un aumento de uso de la plataforma, conlleva un aumento de actividades por parte del docente. Como ha señalado Guri-Rosenblit (2018), los estudiantes percibe con claridad cuando sus docentes no se encuentran preparados para la desarrollar su actividad profesional en contextos virtuales, lo que los lleva a desentenderse y despreocuparse por la formación.…”
Section: Discusión De Resultados Y Conclusionesunclassified
“…Sin embargo, muchos estudios han demostrado (Blin & Munro, 2008;Garrote, & Pettersson, 2007;Mahdizadeh, Biemans, Mulder, 2008, Hsu, 2011 que, en la docencia virtual, la mayoría de actividades realizadas, cumplen características de un modelo centrado más en transmitir, que en crear y construir conocimientos; hecho que, desde nuestro punto de vista, viene motivado, por el tipo de formación técnica y didáctica que posea el docente, y por la frecuencia y tipo de uso que haga de la plataforma y que condiciona la realización de actividades más diversas e innovadoras (Badia, Garcia y Meneses, 2017;Luo, et al, 2017;Ramirez y Barajas, 2017).…”
Section: Introducción: La Formación a Través De Plataformas Virtualesunclassified
“…Gonzalez found that student characteristics and institutional influence had a direct impact on how teachers approach their teaching, while curriculum and subject only had an indirect influence. Additionally, Badia, Garcia, and Meneses (2016) found that time invested in teaching is related to teachers' approaches to teaching.…”
Section: Extrinsic Factors In Digital Teaching Contextsmentioning
confidence: 99%